Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. PLN (Persero) Rayon Jawi Pontianak - Anita Librianty; Rudi Triadi Yuliarto (STIE Widya Manggala, 2019)
The purpose of this research is to examine the influence of obedience and compensation to performance at the office of the regional secretariat of Pontianak. The sample was 70 employees. The data was collected through questionnaire and analyzed with multiple linier regression. The result showed that obedience has a positive significant relationship to performance, while compensation didn’t have relationship to performance at the office of the regional secretariat of Pontianak.